Rancang Bangun Sistem Penjualan Sate Taichan Berbasis Web - Mulyadien, Muhamad Khandava; Kurniawan, Adi; Utami, Dwiarti Rahma; Enri, Ultach (STIKOM Tunas Bangsa Pematangsiantar, 2022)
An e-commerce Website is a Website to aims to sell one or more goods or services by using electronic media as a media for the transaction of goods/services. Taichandel is a food outlet that sells a variety of foods, Aim of this research to solve the problem that occurs at the Taichandel because the transaction of this outlet still manual. The metodh of this research using waterfall metodh, this metodh is used to develop the software start with analytic, design, code until testing. The results of this research is design system and system implementation with programming languages as html, php and database MySQL. Benefit of this research is this information system can help the process of managing data related to the Taichandel Store and speed up the process of buying, selling and selling transactions and also the owners can check the transaction reports because all store data is stored in the database so as to maximize sales evaluation and minimize loss of sales data.